Pengaruh Content Marketing dan Affliate Marketing terhadap Minat Beli Fashion pada Media Sosial Tiktok: (Studi Kasus Genersi Z di Kota Prabumulih) - Bayu Aditya Syahputra; Nurmayanti Nurmayanti; Phinton Panglipur (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The rapid development of social media, particularly TikTok, has significantly transformed the consumption behavior of Generation Z and encouraged businesses to use the platform as a strategic digital marketing medium for fashion products in Prabumulih City. This study aims to examine the influence of content marketing and affiliate marketing on the purchase intention of Generation Z TikTok users toward fashion products. The research applied a quantitative approach with descriptive and associative methods. Respondents were selected through purposive sampling based on the criterion that they were members of Generation Z who actively used TikTok. Data were collected using a questionnaire measured with a Likert scale and analyzed to determine the relationship between the research variables. The results show that content marketing and affiliate marketing both have positive effects on purchase intention, with affiliate marketing demonstrating a more dominant influence than content marketing. Together, the two variables explain 56.9% of the variation in purchase intention, while the remaining 43.1% is influenced by other factors outside the research model. These findings confirm that optimizing TikTok-based content marketing and affiliate marketing strategies can effectively increase the purchase intention of fashion products among Generation Z.